Contemporary Challenges of Spatial Planning in Tourism Destinations - Tomasz Napierała, Katarzyna Leśniewska-Napierała, Giancarlo Cotella (Łódź University Press, 2023)
The book entitled “Contemporary challenges of spatial planning in tourism destinations” compares the different contexts for spatial planning and how they approach tourism-related issues in selected European countries, namely Italy, Norway, Poland, Portugal and Turkey. Each chapter starts with a presentation of the overall profile of the investigated country. The chapters then consider the following contexts of spatial planning of tourism destinations: legal regulations of spatial planning, long-term strategy for spatial planning, public participation in spatial planning, and the main challenges of spatial planning of tourism destinations. The publication ends with an overarching discussion focusing on the various challenges that affect sustainable spatial planning of tourism destinations in the countries under consideration. The book was edited by Tomasz Napierała and Katarzyna Leśniewska-Napierała (both from University of Lodz), and Giancarlo Cotella (Politecnico di Torino). The publication is the output of the international project SPOT – Sustainable Spatial Planning of Tourism Destinations, supported by the European Commission under the Erasmus+ Programme (2019-1-PL01-KA203-064946). Celem anglojęzycznej książki zatytułowanej “Contemporary challenges of spatial planning in tourism destinations” (Współczesne wyzwania planowania przestrzennego destynacji turystycznych) jest porównanie różnych kontekstów planowania przestrzennego ważnych z perspektywy rozwoju turystyki w wybranych krajach europejskich (Włoszech, Norwegii, Polsce, Portugalii i Turcji). Każdy z rozdziałów rozpoczyna się prezentacją najważniejszych informacji na temat badanego kraju. W dalszej kolejności omawiane są różne wymiary planowania przestrzennego destynacji turystycznych: regulacje prawne planowania przestrzennego, długookresowa strategia planowania przestrzennego, znaczenie partycypacji społecznej w planowaniu przestrzennym oraz główne wyzwania planowania przestrzennego destynacji turystycznych. Całą publikację podsumowuje ogólna dyskusja nad czynnikami, które współcześnie mają największy wpływ na zrównoważone planowanie przestrzenne destynacji turystycznych w badanych krajach. Książkę zredagowali Tomasz Napierała i Katarzyna Leśniewska-Napierała (oboje z Uniwersytetu Łódzkiego) oraz Giancarlo Cotella (Politecnico di Torino). Publikacja powstała w efekcie realizacji międzynarodowego projektu SPOT – Sustainable Spatial Planning of Tourism Destinations, dofinansowanego przez Komisję Europejską w ramach programu Erasmus+ (2019-1-PL01-KA203-064946).